Effect of NK cell immunotherapy on immune function in patients with hepatic carcinoma: A preliminary clinical study. Issue 5 (4th May 2017) - Qin, Zilin; Chen, Jibing; Zeng, Jianying; Niu, Lizhi; Xie, Silun; Wang, Xiaohua; Liang, Yingqing; Wu, Zhenyi; Zhang, Mingjie
ABSTRACT: We investigated the effectiveness of adoptive transfer of KIR ligand-mismatched highly activated nature killer (HANK) cells in patients with hepatic carcinoma. Peripheral blood mononuclear cells were obtained and cultured in vitro to induce expansion and activation of HANK cells. After 12 d of culture, the cells were divided into 3 parts and infused intravenously on days 13 to 15. The patients (n = 16) were given one to 6 courses of immunotherapy. No side effects were observed. The lymphocyte subsets and cytokine, thymidine kinase 1 (TK1) and circulating tumor cell (CTC) levels were measured 1 day before treatment and 1 month after the final infusion: the absolute number of total T cells and NK cells and the IL-2 and TNF-β levels were significantly higher, and the TK1 and CTC levels were significantly lower at 1 month after treatment. The percentage of patients who experienced partial response, disease stabilization, and disease progression at 3 months after treatment was 18.8%, 50.0% and 31.2%, respectively. The total follow-up period was 2–12 months. The median progression-free survival from treatment was 7.5 months. This is the first study on the benefits of HANK cell immunotherapy for hepatic carcinoma These encouraging preliminary observations imply that HANK cell immunotherapy is safe, can improve the immune function of patients with liver cancer, and may even reduce the rate of tumor metastasis and recurrence. However, further studies on larger samples of patients with a longer follow-up period are required to confirm these findings.